A behavioral analysis of verbal reports and parental educative practices: scope and limits - Leme, Vanessa Barbosa Romera; Bolsoni-Silva, Alessandra Turini; Carrara, Kester (Paidéia (Ribeirão Preto), 2009)
This study addresses the relevance of some methodological strategies of the Applied Behavior Analysis to examine parental educative practices. An instrument and a concept related to the data collection and analysis are discussed from a theoretical and applied perspective: verbal reports and descriptive functional behavioral analysis. The conclusion, considering the limitations of the reports, is that the information acquired using this strategy in addition to the descriptive functional behavioral analysis permitted the inference of some hypotheses concerning the behavior of parents and children, which can be used in actions aimed to investigate and intervene on behavioral problems and social skills.